How Could Paul Accuse Peter of "Living Ethné-ishly" in Antioch (Gal 2:11-21) If Peter Was Eating according to Jewish Dietary Norms? - Nanos, Mark D. (Journal for the study of Paul and his letters, 2016)
The prevailing readings of the Antioch incident depend on a number of assumptions about the relevant context, including more than a few that remain unexamined, on which several central interpretive decisions about Paul's language depend. These include a fundamental conflict between Pauline and Jerusalem- or Jewish-based Christ-following groups and, following from this, that the mixed meal-time gathering Paul discussed was not conducted according to Jewish dietary norms but instead according to Pauline and thus presumably non-Jewish standards. That is, when Paul accused Peter and the other Jews involved of "living like Gentiles," Paul thought not only that they should do so but that this consisted of behavior like eating without regard for Jewish dietary halakhah. Traditional as well as New Perspective approaches such as these might be classified as based on and leading to "Paul, not Judaism" readings. This essay challenges these and similar assumptions and related decisions by conducting a close review of Paul's language and the assumptions from which Paul seems to work (as well as the others to whom he refers or writes) and offers a reading based on a very different set of assumptions and decisions that results in a "Paul within Judaism" alternative.